Patriotic Philosophy Values as a Driving Factor of Development of Kazakhstan - KABAYEVA, Z; IMANMOLDAYEVA, B; ZHANBAYEVA, Z; MADALIEVA, Z (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Each nation has its own system of values, which is currently under threat in the context of globalization and integration processes. By way of comparative, qualitative, quantitative and dialectic analysis, the study examines the influence of values of the national philosophy on the development of various spheres of Kazakhstani society and overall development of the country. The results of the study show that the nationally accepted and supported philosophy as set of ethical values, like the Eternal Country, significantly contributes to sustainable development of the country and positively impacts various dimensions of life, including social, economic and cultural spheres. RESUMEN Cada nación tiene su propio sistema de valores, que actualmente está amenazado en el contexto de los procesos de globalización e integración. Mediante un análisis comparativo, cualitativo, cuantitativo y dialéctico, el estudio examina la influencia de los valores de la filosofía nacional en el desarrollo de diversas esferas de la sociedad kazaja y el desarrollo general del país. Los resultados del estudio muestran que la filosofía aceptada y respaldada a nivel nacional como un conjunto de valores éticos, como el País Eterno, contribuye significativamente al desarrollo sostenible del país e impacta positivamente en varias dimensiones de la vida, incluidas las esferas sociales, económicas y culturales.